The relationship between power thrust and power drag in elite short distance swimmers - Zamparo, P.; Cortesi, M.; Gatta, G. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction: At constant average speed (v), a balance between thrust force (Ft) and drag force (Fd) should occur: Ft-Fd = 0 (Toussaint et al. 1992); hence power thrust (Pt = Ft v) should be equal to the power needed to overcome drag forces at that speed (Pd = Fd v); the aim of this study was to measure Pt (full tethered swims) and to estimate Pd in active conditions (at sprint speed) and to compare these values. Methods: Ten front crawl elite swimmers (male; 23.5 ± 3.4 years; expertise 93.1 % ± 2.4 of 50 m world record) participated to the study; their sprint speed was measured during a 30 m all-out trial. Ft was assessed during a 15 s full-tethered effort (Keskinen et al. 1989); passive towing measurement were performed to determine speed specific drag in passive conditions (kP = passive drag force / v2); drag force in active conditions (Fd = kA v2) was calculated assuming that kA = 1.4 kP (Gatta et al. 2015). Results: Average sprint speed was 2.20 ± 0.07 m/s; kA, at this speed, was 34.7 ± 2.5 N/m2/s2. A strong correlation between power thrust (399 ± 56 W) and power drag (374 ± 53 W) was observed: Pd = 2.35+ 0.929.Pt, R2 = 0.953, N = 10, p < 0.001. The Bland-Altman level of agreement was generally less than ± 1.96 SD, the mean difference (± SD) between methods was 25.8 ± 12.2 W. Discussion: In this study, the swimmer power for propulsion was calculated as a product of force and velocity using two different methods. This evaluation shows that the power thrust values have a high degree of agreement with the (active) power drag values and this support the use of the full tethered test as an accurate, reliable test to compute the power propulsion of a swimmer.